Bound by the sea: transnational Sri Lankan writings and reconciliation with the homeland - Jeslyn Sharnita Amarasekera,; Shanthini Pillai, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
For most transnational Sri Lankans, the ethnic conflict that has submerged the island is often positioned as a significant aspect of their lives. Many transnational writers tend to focus on the ethnic conflict as well as the aftermath of leaving the homeland. Despite leaving, the homeland and the memories of the island tend to travel with the transnationals as they move to a new home. One crucial aspect of the memory of the homeland is the sea which surrounds the island. The sea is often perceived as an image that binds them to their homeland. The sights and sounds of the sea often offer both pleasant and traumatic memories, especially for those who have left the homeland. With this in mind, this paper seeks to discuss the ways in which selected transnational writers of Sri Lanka present their memories of the homeland as expressed through the image of the sea. This paper will probe into two novels by transnational Sri Lankan writers; Nayomi Munaweera’s Island of A Thousand Mirrors and Randy Boyagoda’s Beggar’s Feast. The discussion will be framed by Avtar Brah’s notion of home, as being found within the “lived experiences of a locality”. The images of the sea as presented by these writers will then be used to determine the possibility of reconciliation with the homeland or the perpetuation of trauma.